The Research of the Domain of Permissible Braking Modes of Cuts on the Gravity Humps - Bobrovskyi, Volodymyr I.; Kozachenko, Dmitriy N.; Dorosh, Andrii S.; Demchenko, Evhen B.; Bolvanovska, Tetiana V.; Kolesnyk, Anton I. (Silesian University of Technology, Katowice, 2015)
ENG: The paper presents the research results of cuts braking modes on the gravity humps. The objective of this paper is developing the methods for assessment of braking modes of cuts under conditions of fuzziness of their rolling properties, as well as select-ing the permissible starting speed range of cuts from retardant positions. As a criterion for assessing the modes of target control of cut rolling speed, it was proposed to use an aver-age gap size on a classification track at the established norms of probable exceeding of permissible speed of cars collision and their stop in retarders. As a criterion for evaluating the modes of interval control of cuts rolling speed, using the risk of their non-separation on the switches was proposed. Using the simulation modeling and mathematical statistics, the configuration of the domain of permissible speed of cuts coming out from retardant positions has been set. The conducted researches allow simplifying the choice of cut braking modes in systems of automatic control of cut rolling speed.

UKR: У статті представлені результати досліджень режимів гальмування відчепів на сортувальних гірках. Метою статті є розробка методів оцінки режимів гальмування відчепів в умовах невизначеності їх ходових характеристик, а також пошук області допустимих швидкостей виходу відчепів з гальмівних позицій. В якості критерію для оцінки режимів прицільного регулювання швидкості скочування відчепів запропоновано використовувати середню величину вікна на сортувальній колії при встановлених нормах ймовірності перевищення допустимих швидкостей співудару вагонів і зупинки їх у сповільнювачах. В якості критерію для оцінки режимів інтервального регулювання швидкості скочування відчепів запропоновано використовувати ризик їх нерозділена на стрілках. За допомогою методів імітаційного моделювання та математичної статистики встановлена конфігурація області допустимих суперечливість виходу відчепів з гальмівних позицій. Виконані дослідження дозволяють спростити рішення задачі вибору режимів гальмування відчепів у системах автоматичного керування швидкістю їх скочування.

RUS: В статье представлены результаты исследований режимов торможения отцепов на сортировочных горках. Целью статьи является разработка методов оценки режимов торможения отцепов в условиях неопределенности их ходовых характеристик, а также поиск области допустимых скоростей выхода отцепов из тормозных позиций. В качестве критерия для оценки режимов прицельного регулирования скорости скатывания отцепов предложено использовать среднюю величину окна на сортировочном пути при установленных нормах вероятности превышения допустимых скоростей соударения вагонов и остановки их в замедлителях. В качестве критерия для оценки режимов интервального регулирования скорости скатывания отцепов предложено использовать риск их неразделения на стрелках. С помощью методов имитационного моделирования и математической статистики установлена конфигурация области допустимых споростей выхода отцепов из тормозных позиций. Выполненные исследования позволяют упростить решение задачи выбора режимов торможения отцепов в системах автоматического управления скоростью их скатывания.
Дослідження області допустимих режимів гальмування відчепів на сортувальних гірках
Исследование области допустимых режимов торможения отцепов на сортировочных горках
V. Bobrovskyi: ORCID 0000-0001-8622-2920; D. Kozachenko: ORCID 0000-0003-2611-1350; A. Dorosh: ORCID 0000-0002-5393-0004; T. Bolvanovska: ORCID 0000-0001-6462-8524; Е. Demchenko: ORCID 0000-0003-1411-6744; А. Kolesnik: ORCID 0000-0003-2490-5843
Keywords: braking; cut; gravity hump; гальмування; відцеп; сортувальна гірка; торможение; отцеп; сортировочная горка; КСВ; НДЧ; КУЕР